Assessment of functionalities and attitude toward telemedicine for patients with cardiovascular disease - Lieselotte Knaepen; Maarten Falter; Martijn Scherrenberg; Paul Dendale; Lien Desteghe; Hein Heidbuchel (Digital Health, 2023)
Introduction Many patients with cardiovascular diseases are only seen by a physician once or twice a year unless urgent symptoms. Recent years have shown an increase in digital technologies to follow patients remotely, that is, telemedicine. Telemedicine can be supportive for follow-up of patients at continuous risk. This study investigated patients’ attitude toward telemedicine, the defined features they consider important and future willingness to pay. Methods Cardiology patients with various types of prior telemedicine follow-up or who never had a telemonitoring follow-up were included. A new self-developed survey was implemented electronically and took 5–10 min to complete. Results In total, 231 patients (191 telemedicine [T] and 40 controls [C]), were included. Most participants owned a smartphone (84.8%) and only 2.2% of the total participants did not own any digital device. The most important feature of telemedicine cited in both groups was personalization (i.e., personalized health tips based on medical history, 89.6%; personalized feedback on entered health parameters 86.1%). The most important motivating factor for the use of telemedicine is recommendation by a physician (84.8%), while the reduction of in-person visits is a minor reason (24.7%). Only half of the participants (67.1%) would be willing to pay for telemedicine tools in the future. Conclusion Patients with cardiovascular disease have a positive attitude to telemedicine, especially when it allows for more personalized care, and when it is advocated by the physician. Participants expect that telemedicine becomes part of reimbursed care. This calls for interactive tools with proven efficacy and safety, while guarding unequal access to care.